Perbandingan Bentuk Wajah Antara Mahasiswa-Mahasiswi Suku Jawa Dan Suku Ternate - Nursyafat Arsyad; Hastoro Pintadi (Universitas Muhammadiyah Yogyakarta, 2007)
Java ethnic was Mongoloid race, while Ternate tribe was Austromelanesoid race. The aim of research is to compare facial indekx between Javaness and Ternateness by measuring the facial width and the facial height.This research is cross sectional by the subject of research was 20 adult Javanese group and 20 adult Ternate etnic group whose live in Yogyakarta which each divided in 2 groups male and female. Inﬂuence variable is ethnic and to have inﬂuence variable is facial shape. Subject criteria which used was students in age 18-25 years old both from native Javanese and ternate etnic, which is not wear ortho appliance, in health condition and no facial deformity. The variable which uncontrolled was nutrition and bad habbit. The subject which fulﬁll measured their facial breadth and facial hight. Facial width measured from right zigion until left zigion use spreading caliper; and hight facial measured from nasion to gnathion uses sliding caliper: The result of width and hight facial was found from facial index which have been taken ration population from both ethnics. The result was measured analized useed t-tes.The result showed that there was no signiﬁcant diﬂerences facial index between those two etnic (p0.05). Facial index between Javanese and Ternatenese male t=0.1 78, p=0.861. Facial index between Javenese and Ternatenese female t=1.283, p=0,216. from the result can be conclude that: 1). There is no differential hight and width facial between Javanese and T ernatenese female, 2). There no was differential hight and breadth facial between Javanese and Ternatenese male, 3). There was no differential facial index between Javanese and Ternatenese.